Surrogacy Explored: The Impact on Carriers and Their Experiences Internationally - Aslam, Mohammad; Singh, Uday Veer (Journal of Neonatal Surgery, 2025)
Surrogacy is an essential fertility intervention for persons encountering medical issues or infertility, including same-sex couples and single males. This study examines the psychological, physical, and socio-cultural aspects of surrogacy in several worldwide contexts, including the United Kingdom, Canada, the United States, and India. The study contrasts altruistic and commercial surrogacy models, emphasizing the emotional and mental health outcomes of surrogate mothers and exposing differences shaped by cultural, legal, and financial variables. Significant studies reveal that surrogacy experiences can be advantageous, as numerous surrogates sustain rewarding connections with intended parents; nonetheless, challenges such as stigma, mental health hazards, and exploitation remain prevalent. The document examines the ramifications for infants conceived through surrogacy, focusing on birth outcomes and possible psychological effects. This comparative analysis recommends for enhanced laws and support systems for surrogates, highlighting the necessity for complete legal frameworks that protect their rights and welfare.